Comparative proteomic analysis reveals the pathological mechanisms of overuse achilles tendinopathy and the therapeutic mechanisms of ESWT and PRP - Gongzi Zhang; Tianshu Zhao; Yangxiaoxue Liu; Jianing Xu; Wenxi Luo; Hao Liu; Bei Liu; Jingxian Hou; Jiali Zhang; Ruining Wu; Ming Zhou; Liping Huang (Tissue and Cell, 2026)

An electrochemical sensor for ultrasensitive and wide-range detection of the food additive potassium ferrocyanide based on signal attenuation mechanism of a poly(caffeic acid) film - Suozhu Wu; Xuedong Jia; Zhuo Shi; Ruining Liu; Yujia Liu; Hongyuan Guo (Food Chemistry, 2026)

Hybrid vesicle-camouflaged cascade nanoreactors enable dual-targeted ferroptotic killing of intracellular MRSA and immune remodeling in pneumonia - Siyuan Yu; Yueru Pang; Ziqi Shen; Feiyang Liu; Ruixin Kang; Wei Li; Ruining Li; Lin Luo; Junyan Zhang; Qi Shen (Chemical Engineering Journal, 2026)

Excavation-induced principal stress rotation and deformation responses in shallow-buried tunnels - Hongguang Jiang; Siwei Ruan; Ruining Liu; Xizhen Song; Yixin Li; Shun Liu; Xinyu Wang; Chenglu Gao; Zhanyong Yao; Chuanyi Ma (Transportation Geotechnics, 2026)

Hyoscyamine Ameliorates Repetitive Behavior in NLG1 and SHANK3 Deficient-Mice - Dandan Lv; Ruining Liu; Xinyu Zhang; Siqi Peng; Wei Xie; Mingdao Mu; An Liu (Neuroscience Bulletin, 2026)

Advances in targeted nutrient delivery: materials design and mechanistic perspectives for precision nutrition - Yi Wang; Guannan Liu; Ruining Zhang; Yaqiong Wang; Pei Wang; Chong Xie; Hansong Yu; Runqiang Yang (Food Research International, 2026)

Integrated analysis of laboratory and field experiments to screen rice germplasm for submergence tolerance across various growth stages - Shengqin Liu; Hao Ai; Sumei Duan; Ruining Li; Edwin Afriyie Owusu; Liangliang Lv; Zhanglun Sun; Dachao Xu; Mengzhu Zhang; Aifeng Zhou; Wei Wang; Tingting Feng; et al. (Field Crops Research, 2026)

Ultraviolet-treated riboflavin induces ROS-mediated apoptosis via inhibiting mitochondrial complex I in acute myeloid leukemia - Ruining Liu; Shuang Ge; Jinyuan Sun; Yi Liu; Liping Sun; Yang Yu; Deqing Wang (Journal of Photochemistry and Photobiology B: Biology, 2026)

Bifunctional modulation of MrBBX19 on repressor MrNAC47 and activator MrMYB12 for UV-B-mediated quercetin enhancement in Chinese bayberry (Morella rubra) - Ruining Zhang; Qianyu Wang; Jiajia Li; Jiafei Qian; Xiangrui Cui; Yunlin Cao; Yilong Liu; Xiaoyong Zhao; Di Wu; Changjie Xu; Kunsong Chen; Xian Li (Food Chemistry, 2026)

Biogeochemical nitrogen cycle response to Middle Permian climate warming in Northwest China paleolake - Xueqi Song; Ruining Hu; Wenquan Xie; Jinqi Xu; Xin Liu; Haibo Xu; Jingqiang Tan; Thomas J. Algeo (Global and Planetary Change, 2025)

Ultrasensitive and rapid electrochemical detection of nitrite based on gold nanoparticles-poly(phenylboronic acid) modified electrode and I2/I− probe - Xuedong Jia; Hongyuan Guo; Xiu Zhao; Ruining Liu; Xiayu Song; Zhuo Shi; Yingchun Zhu; Suozhu Wu (Food Chemistry, 2025)

Soybean insoluble Fiber-EGCG binary compounds: Enhanced stability and synergistic antioxidant activity - Yi Wang; Ruining Zhang; Shidi Men; Mingzhe Li; Guannan Liu; Xiangbo Zeng; Bo Lyu; Sainan Wang; Hansong Yu (Food Chemistry, 2025)

SAR ship detection across different spaceborne platforms with confusion-corrected self-training and region-aware alignment framework - Shuang Liu; Dong Li; Haibo Song; Caizhi Fan; Ke Li; Jun Wan; Ruining Liu (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

MbWRKY50 confers cold and drought tolerance through upregulating antioxidant capacity associated with ROS scavenging - Xinhui Wang; Yingnan Li; Zhuo Chen; Longfeng Li; Qiqi Li; Zihan Geng; Wanda Liu; Ruining Hou; Lihua Zhang; Deguo Han (Journal of Plant Physiology, 2025)

Phytochemical investigation of Jie-Geng-Tang and regulatory role in the TNF-α pathway in mitigating pulmonary fibrosis using UPLC-Q-TOF/MS - Bingxin Li; Ruining Zhao; Xiaojie Jiang; Chang Liu; Yun Ma; Haijun Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Long-term soy dietary fiber diet modifies the intestinal internal environment: Focus on chronic ulcerative colitis - Yi Wang; Ruining Zhang; Mingzhe Li; Jiaxin Li; Guannan Liu; Sainan Wang; Bo Lyu; Hansong Yu (Food Research International, 2025)

Effects of Glutamate on Growth Performance, Gut Digestion and Antioxidant Capacity in Juvenile Little Yellow Croaker - Ruining Liu; Yu Zhang; Xiao Liang; Bao Lou; Junquan Zhu (Fishes, 2025)
This study is to explore the alleviating effects of glutamate on intestinal damage in cultured little yellow croaker. A total of 900 juvenile fish at a weight of 30.68 ± 0.12 g were randomly separated into six groups with three replicates each, and were fed a basic diet (protein at 44.42% and lipid at 12.48%) with additional glutamate at 0.00%, 0.40%, 0.80%, 1.2%, 1.60%, and 2.00%. Each replica group consisted of 50 fish in a breeding barrel (radius 1.0 m, height 1.5 m), and the experiment lasted for 54 days. The results showed that supplementation with 0.4–1.2% glutamate significantly improved the survival rate, which increased from 75.56% to 91.11%, reduced the feed conversion rate from 1.75 to 1.57, and increased the protein efficiency ratio from 1.55 to 1.85 (p

Exploring the preventive effects of Jie Geng Tang on pulmonary fibrosis induced in vitro and in vivo: a network pharmacology approach - Bingxin Li; Xiaojie Jiang; Chang Liu; Yun Ma; Ruining Zhao; Haijun Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

A comprehensive experimental and theoretical study of thermal response mechanisms of TKX-50 and HMX - Xuan Ren; Ruining He; Xinhui Wang; Fang Wang; Xinpeng Zhang; Dingcheng Wang; Shuyuan Liu; Henry J. Curran; Jinhu Liang; Yang Li (Fuel, 2024)

Cleaner reactive dyeing with the recycled dyeing wastewater - Dawu Shu; Wanxin Li; Bo Han; Fangfang An; Yan Zhang; Shaolei Cao; Ruining Liu (Journal of Environmental Chemical Engineering, 2024)

Priority bacteria causing biofouling of reverse osmosis membranes: Potential disinfection-resistant bacteria and control strategies - Yujia Gao; Haobin Wang; Yuqing Xu; Ruining Wang; Han Liu; Yu Qiu; Yu Hong; Hongying Hu; Yinhu Wu (Desalination, 2024)

Weakened hydrological oscillation period increased the frequency of river algal blooms - Qiang HU; Yan CHEN; Rui XIA; Xiaoyu LIU; Ruining JIA; Kai ZHANG; Xiaoxuan LI; Chao YAN; Yao WANG; Yingze YIN; Xiang LI; Junde MING (Water Research, 2024)

Coupling of nitrogen biogeochemical cycling and phytoplankton community structure before and after the Late Ordovician mass extinction in South China - Ruining Hu; Jingqiang Tan; Wenhui Wang; Xueqi Song; Philip A.E. Pogge von Strandmann; Jeffrey Dick; Chiyang Liu (Chemical Geology, 2024)

Performance and mechanisms of zero valent iron enhancing short-chain fatty acids production during thermophilic anaerobic fermentation of waste activated sludge - Wanqing Ding; Xiumin Fan; Xu Zhou; Ruining Liu; Chuan Chen; Wenbiao Jin; Jing Sun; Xuan Li; Guangming Jiang; Huan Liu (Science of The Total Environment, 2024)

Probing the combustion kinetics of dimethylformamide: A theoretical study of H-atom abstraction reactions - Xin Bai; Yang Li; Shuyuan Liu; Ruining He; Jinhu Liang; Geyuan Yin; Shijie Zheng; Yan Qian; Xuebin Wang (Fuel, 2023)

Machine learning models based on residue interaction network for ABCG2 transportable compounds recognition - Ruining Guan; Wencheng Liu; Ningqi Li; Zeyang Cui; Ruitong Cai; Yawei Wang; Chunyan Zhao (Environmental Pollution, 2023)

Depositional conditions of siliceous microfossil-rich shale during the Ordovician–Silurian transition of south China: Implication for organic matter enrichment - Ruining Hu; Jingqiang Tan; Jeffrey Dick; Yong Wang; Guolai Li; Chiyang Liu (Marine and Petroleum Geology, 2023)

The development process of plant-based meat alternatives: Raw material formulations and processing strategies - Yi Wang; Bo Lyu; Hongling Fu; Jiaxin Li; Lei Ji; Hao Gong; Ruining Zhang; Jingsheng Liu; Hansong Yu (Food Research International, 2023)

Correction to: Linarin Protects against Cadmium-Induced Osteoporosis Via Reducing Oxidative Stress and Infammation and Altering RANK/RANKL/OPG Pathway - Yating Yang; Ruining Cheng; Jingyun Liu; Jing Fang; Xiaojing Wang; Yingxue Cui; Pan Zhang; Bin Du (Biological Trace Element Research, 2022)

Linarin Protects against Cadmium-Induced Osteoporosis Via Reducing Oxidative Stress and Inflammation and Altering RANK/RANKL/OPG Pathway - Yating Yang; Ruining Cheng; Jingyun Liu; Jing Fang; Xiaojing Wang; Yingxue Cui; Pan Zhang; Bin Du (Biological Trace Element Research, 2022)

Improving sulforaphane content in transgenic broccoli plants by overexpressing MAM1, FMOGS–OX2, and Myrosinase - Haiyan Cao; Ruining Liu; Jinhua Zhang; Zhiqiang Liu; Sanhong Fan; Guangdong Yang; Zhuping Jin; Yanxi Pei (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Maribellus comscasis sp. nov., a novel deep‐sea Bacteroidetes bacterium, possessing a prominent capability of degrading cellulose - Rikuan Zheng; Ruining Cai; Rui Liu; Ge Liu; Chaomin Sun (Environmental Microbiology, 2021)
Summary Bacteroidetes are thought to be specialized for the degradation of algae‐derived ocean polysaccharides. Here, we show that Bacteroidetes are the predominant phylum in deep‐sea sediments and possess more genes associated with polysaccharides degradation than other bacteria. We have isolated a novel Bacteroidetes species from the deep‐sea sediments by using a special polysaccharide containing medium, Maribellus comscasis WC007, which possesses 82 putative polysaccharide utilization loci (PULs) containing 374 glycoside hydrolases and 82 SusC/D pairs (Sus indicates s tarch u tilization s ystem; SusC represents the actual TonB‐dependent transporter, and SusD is an associated substrate‐binding outer membrane lipoprotein) together with 58 sigma/antisigma factors. Through an in‐depth analysis of these PULs, strain WC007 can efficiently degrade numerous different polysaccharides including cellulose, pectin, fucoidan, mannan, xylan and starch, which are verified by growth assays. Notably, we find that cellulose has the most significant growth‐promoting effect on M . comscasis WC007. And based on scanning electron microscope observation, transcriptomics and metabolomics, we further report on the underlying mechanisms of cellulose degradation and utilization, as well as potential contributions to the carbon cycle. Overall, our results suggest that Bacteroidetes may play key roles in the carbon cycle, likely due to their high abundance and prominent polysaccharide degradation capabilities.